Responsabilidade socioambiental na Universidade Federal de Sergipe : princípios e práticas para a promoção da sustentabilidade - Matias, Sandra Lucia Alves (2014)
The implementation of environmental management tools to prevent and control environmental damage arising from administrative and operational activities is a necessary and urgent reality within the institutions which are members of the public administration. In this sense, the Federal Government, anxious to reduce negative environmental impacts and promote the internalization of environmental responsibility, created the Environmental Agenda of Public Administration - A3P through the Ministry of Environment. This agenda aims to stimulate reflection and change of attitude of the servers so that they incorporate the criteria of environmental management into their routine activities and it also aims to raise awareness among public managers to environmental issues. Given the importance that public institutions have to lead by example, this agenda has been structured into five priority themes: rational use of natural resources and public goods; proper management of waste generated; quality of life in the workplace, awareness and training of the servers and sustainable procurement . In general terms, the research aimed to characterize environmental initiatives developed at the Federal University of Sergipe in relation to themes of the Environmental Agenda in Public Administration (A3P). To carry out the research, methodological tools grounded in phenomenology were employed. The methods chosen were the exploratory and the descriptive survey with qualitative and quantitative data. To do so, we performed semi-structured interviews with managers, teachers , administrative staff and students . The results showed that environmental management initiatives in the institution, even partially, are in harmony with the axes of the A3P. Therefore, there is need for greater commitment on the part of managers and servers with the environmental problems in the pursuit of a sustainable culture .